Saturation evaluation of tight sandstone in the Dayi structure, West Sichuan Depression - Guo, Yuhao; Sima, Liqiang; Wang, Liang; Miao, Xiangxi; Li, Angxing; Su, Shute (Frontiers in Earth Science, 2023)
Abstract: Tight sandstone reservoirs are characterized by poor physical properties, strong heterogeneity, and complex pore structures, resulting in low reservoir saturation calculation accuracy, and the log interpretations do not match the gas test results. In response to the above problems, the tight sandstone reservoir of the third member of the Xujiahe Formation of the Dayi Structure in the Western Sichuan Depression was investigated through a series of experiments on petrophysical properties, casting thinsection identification, rock resistivity, nuclear magnetic resonance, and high-pressure mercury intrusion.Then, after a systematic analysis of the influence of different factors, including physical properties, mineral composition, and pore structure, on the rock-electric parameters, the parameters of the Archie model were appropriately corrected. The results showed that, for tight sandstone reservoirs, the cementation exponent was mainly affected by the physical properties and clay content, and the saturation exponent was controlled by the proportion of relatively large pore components in the total pore system. Therefore, the nonlinear least squares method was used to construct the variable cementation index model; the pseudo-capillary pressure curve was constructed, and a new parameter "the large-pore proportion," which is used to optimize the saturation exponent, was proposed in combination with the fractal theory.Finally, an Archie model with variable parameters was used to process the actual logging data in the study area. The results show that this method can obtain a more accurate gas saturation, providing a new idea and method for fine sandstone saturation logging evaluation.